Hypoxic training: Effect on mitochondrial function and aerobic performance in hypoxia - Robach, P.; Bonne, T.; Flück, D.; Bürgi, S.; Toigo, M.; Jacobs, R. A.; Lundby, C. (Medicine & Science in Sports & Exercise, 2014)
Purpose: The effects of hypoxic training on exercise performance remain controversial. Here, we tested the hypotheses that i) hypoxic training possesses ergogenic effects at sea level and altitude and ii) the benefits are primarily mediated by improved mitochondrial function of the skeletal muscle.